STRATEGI PEMASARAN DALAM MENINGKATKAN PENGUNJUNG DI DANAU KEMUNING LAMPUNG TIMUR - Pipit Afifah; Edi Jatmiko; Moh. Abdur Rahman Wahid (EKSYDA: Jurnal Studi Ekonomi Syariah, 2023)
East Lampung has a lot of tourism including tourism on the Yellow Lake which is in Seda Srimenanti, Sribawono District. This study aims to determine the marketing strategy and efforts that must be made to increase visitors. The method used is the cumulative method by collecting data from the management and carrying out observations and documentation on Lake Kemuning. The results of this study are that the strategy carried out to increase visitors to the Kemuning Lake tourism shows that the marketing mix in the promotion aspect still relies on the role of consumers who promote by posting photos on social media accounts. As for what is being done to increase visitors by providing facilities and infrastructure so that old visitors will feel comfortable returning to visit and make it attractive to potential visitors who are looking for tourist sites. Efforts that must be made to increase visitors are by utilizing social media, greening and increasing human resources.